Alveolar ridge preservation in a growing patient with decoronation: One-year follow-up - Astha Jaikaria; Seema Thakur (Wolters Kluwer Medknow Publications, 2019)
Dentoalveolar ankylosis in growing patients is associated with continuing replacement root resorption, tooth infrapositioning, and the local arrest of alveolar bone growth. While extraction of ankylosed teeth might be associated with bone loss, decoronation of the offending tooth (removal of crown portion and instrumentation of pulp canal to stimulate bleeding) has been suggested as a more conservative approach of bone preservation until definitive implant placement is planned. This is a case presentation of a 14-year-old patient who presented with root resorption in relation to the left maxillary central incisor such that decoronation with a prosthetic tooth replacement was decided as the treatment option.